O poder de compras governamental como instrumento de desenvolvimento tecnológico: Análise do caso Brasileiro - Flávia de Holanda Schmidt Squeff (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Public procurement refers to the process through which the government seeks to obtain services, materials and equipment needed to operate in accordance with laws and regulations. Although public procurement is mainly oriented to attend government demands, it is acknowledged by scholars in this field that a more coordinated use of this economic potential can lead to other outcomes that contribute to the process of economic development. In fact, the possibilities of turning public procurement more strategic as a strategy to upgrade productive system have gained prominence recently in Brazilian policies, as illustrated by Plans Brasil Maior and Inova Empresa. Following previous evidence that firms that lagged in marketing capabilities, had low degree of product differentiation and low innovative potential ended up being the biggest beneficiaries of government procurement, this study aims to discuss the use of public procurement, examining data on the profile of industrial firms contracted by Brazilian Federal Government between 2001 and 2010. The analysis uses a stratification of firms according to their share in public procurement vis à vis their share in their sector. This paper updates and expands the work of Soares (2005). Grounded in the literature on demand based innovation policies (DBIP), the central hypothesis of this study is that firms that are more innovative and competitive have not been the most benefited by government's acquisitions. The empirical analysis used a database of 7879 manufacturing firms that were Government suppliers between 2001 and 2010. Firms were identified in Comprasnet, a federal database for public procurement. For each firm in the sample it was calculated, year by year, the coefficient on Government Procurement (in Portuguese, CCG ), a measure suggested by Soares (2005) to indicate that the relationship between the firm's share in government procurement and in firm's market, here understood by their industry subsector. The results confirmed that exporting, innovative and larger firms have an inverse relationship with their CCG.
Keywords: H57; O38; 330; public procurement; demand based innovation policies